Is titanium–zirconium alloy a better alternative to pure titanium for oral implant? Composition, mechanical properties, and microstructure analysis - Ajay Sharma (Elsevier, 2021)
Introduction: Titanium (Ti) is widely accepted as a biomaterial for orthopaedic and dental implants, primarily due to its capacity to integrate directly into the bone and its superior corrosion resistance. It has been suggested that titanium–zirconium alloy (TiZr), with 13–17% of zirconium, has better mechanical properties than pure Ti, but there are very few published studies assessing the suitability of TiZr for high-load- bearing implants. This study aimed to compare the mechanical properties and microstructures of TiZr and commercially pure titanium (Ti). Methodology: Pure Ti and TiZr alloy discs were prepared and subjected to characterisation by nanoindentation, electron dispersive spectroscopy (EDS), X-ray diffraction (XRD), and electron backscatter diffraction (EBSD). Results: The TiZr alloy was found to have significantly lower elastic modulus value (p < 0.0001) and greater hardness than Ti (p < 0.05). The EDS results confirmed the presence of Zr (13–17%) in the TiZr alloy, with XRD and EBSD images showing microstructure with the alpha phase similar to commercially available Ti. Conclusion: The lower elastic modulus, higher hardness, presence of alpha phase, and the finer grain size of the TiZr alloy make it more suitable for high-load-bearing implants compared to commercially available Ti and is likely to encourage a positive biological response.